2019
DOI: 10.1111/jcmm.14696
|View full text |Cite
|
Sign up to set email alerts
|

Variations of Wnt/β‐catenin pathway‐related genes in susceptibility to knee osteoarthritis: A three‐centre case‐control study

Abstract: Excessive activation of the Wnt signalling pathway in the articular cartilage is demonstrated to be related to the onset and severity of osteoarthritis (OA). However, few studies have investigated the association between variants in Wnt‐pathway‐related genes and the risk of OA by searching Pubmed and EMBASE. Totally, 471 knee OA patients and 532 controls were recruited from three hospitals to evaluate the associations of five genetic variants (rs61735963, rs2908004, rs10795550, rs1799986 and rs1127379) with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…According to Huang et al ( 42 ) the regulation of the Wnt signaling pathway reduced the risk of OA. Charlier et al ( 43 ) reported that the DKK3 regulation of the Wnt/β-catenin pathway increased the dedifferentiation of OA chondrocytes in the human hip and promoted the remission of OA.…”
Section: Discussionmentioning
confidence: 99%
“…According to Huang et al ( 42 ) the regulation of the Wnt signaling pathway reduced the risk of OA. Charlier et al ( 43 ) reported that the DKK3 regulation of the Wnt/β-catenin pathway increased the dedifferentiation of OA chondrocytes in the human hip and promoted the remission of OA.…”
Section: Discussionmentioning
confidence: 99%
“…The Wnt pathway is involved in bone and cartilage homeostasis, controls the function of osteoblasts, and affects the differentiation of osteoblasts (Huang et al, 2019;Guo and Cooper, 2007;Li et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The Wnt pathway is involved in bone and cartilage homeostasis, controls the function of osteoblasts, and affects the differentiation of osteoblasts (Huang et al, 2019; Guo and Cooper, 2007; Li et al, 2019). A genome-wide association study revealed that polymorphisms of Wnt4 were associated with bone mineral densities (Hendrickx et al, 2017), which is consistent with the result of our study.…”
Section: Discussionmentioning
confidence: 99%
“… 22 However, this SNP was associated with decreased risk of osteoarthritis in women below 60 whose BMI were greater than or equal to 25. 23 …”
Section: Introductionmentioning
confidence: 99%